Application of modeling and Petri net concepts in the productive process of the sugarcane industry - Yamada, Mamoru Carlos; Porto, Arthur José Vieira; Inamasu, Ricardo Yassushi (Pesquisa Agropecuaria Brasileira, 2002)
The modeling, as a tool of analysis of agribusiness processes as well as of productive chains, supplies the demand for appropriated methodological tools. The present work aimed to evaluate the adherence of modeling and Petri net concepts applied to the sugarcane agroindustrial complex. A real company was used for the acquisition of the information. Models of the chains of activities were validated with the Petri net tool, through an analysis method where all possible paths and all states that the modeled system can reach are simulated. The study resulted in 14 groups of production stages, including all unitary operations of the sugar and alcohol productive chains, from the planting of the cane to the storage of the sugar and alcohol.
Keywords: sugar; alcohol; agroindustrial complex; simulation models